Specific aspects of immunotherapy for multiple sclerosis in Switzerland: A structured commentary. Issue 1 (11th March 2019) - Achtnichts, L; Chan, A; Czaplinski, A; Derfuss, T; Du Pasquier, R; Findling, O; Gobbi, C; Hoepner, R; Kamber, N; Kamm, CP; Kuhle, J; Lalive, P; et al.
More than a dozen substances are meanwhile available for the disease-modifying immunotherapy of multiple sclerosis (MS). However, for some substances, there is a clear difference between approval in Switzerland (Swissmedic) and neighboring countries (European Medicines Agency (EMA)). In addition, limitations imposed by the Swiss Federal Office of Public Health in the specialties list (SL) have significant effects on use in daily clinical practice. In the following, we present consensus recommendations, which were reviewed and agreed upon by the Scientific Advisory Board of the Swiss Multiple Sclerosis Society and the Swiss Neurological Society. We explicitly focus on practice-relevant differences in the approval of MS immunotherapies in Switzerland compared with the EMA area and discuss further limitations (SL) and their impact on the use in clinical practice. Immunotherapies with the same approval in Switzerland and the EMA area and symptomatic therapies are not discussed here.